PENGEMBANGAN POTENSI WISATA AIR DUSUN PANGANCRAAN SEBAGAI DESTINASI WISATA UNGGULAN PENGGERAK EKONOMI LOKAL - Rusliana, Nanang; Susilo, Ignatia Bintang Filia Dei; Paturochman, Iwan Ridwan; Kadarisman, Encang; Rudiana, Dedi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aimed to optimize the water tourism potential of Pangancraan Hamlet, Cijulang, Pangandaran as a driving force of the local economic growth. Despite its natural beauty, which is ideal for river tubing, the tourism sector remains underdeveloped due to limited promotion, uncoordinated tourism management, and declining community enthusiasm for managing tourism activities. Revitalization of the "Cijoelang Rafting" attraction will open up greater local economic opportunities and improve the well-being of the community, while also preserving the environment and local culture. The implementation of the program included four stages: preparation, implementation of counseling, monitoring, and forming an implementation agreement for community partnership programs (fostered villages) with Siliwangi University. The program included outreach efforts to rekindle the community spirit and raise awareness of the importance of effective tourism management. By using a participatory approach that involved the community in decision-making and project implementation, the program sought to ensure the sustainability of tourism management in Pangancraan Hamlet. The participants in the outreach program came from various generations and communities, ensuring that people from all segments of society could gain valuable experiences and insights that could be shared with other group members. Throughout the activity, the participants were actively engaged in interaction and communication.